Measuring Progress in Discourse Production. A genre-based approach - Neumann, Ingrid (HERMES - Journal of Language and Communication in Business, 2000)
The aim of this paper is to find criteria for the evaluation of oral business discourse produced in the language laboratory by students of business German. I felt the lack of an instrument that measures more precisely, not only linguistic criteria like lexis and grammar, but also the pragmatic background and the functions that discourse types within ‘language for specific purposes’ (LSP) have to fulfil. By evaluation I mean the asses-sment of individual progress, but indirectly I evaluate a teaching concept. A good teaching programme should facilitate progress. I am going to describe a teaching concept called Übertragung ‘text transfer’, focusing on the project that provided the data material for the present study. I will then present the model I have chosen as a basis for the study. In the study itself I concentrate on ‘text organisation’ and ‘content structure’.